Institutional Conflicts of Interest in Academic Research - Resnik, David B. (Science and engineering ethics, 2019)
Financial relationships in academic research can create institutional conflicts of interest (COIs) because the financial interests of the institution or institutional officials may inappropriately influence decision-making. Strategies for dealing with institutional COIs include establishing institutional COI committees that involve the board of trustees in conflict review and management, developing policies that shield institutional decisions from inappropriate influences, and establishing private foundations that are independent of the institution to own stock and intellectual property and to provide capital to start-up companies.